目标检测模型的训练方法、目标检测方法及相关设备 (2022)
本申请公开了目标检测模型的训练方法、目标检测方法及相关设备，涉及计算机视觉、深度学习等人工智能技术领域。具体实现方案为：获取训练样本数据，训练样本数据包括第一遥感图像和第一遥感图像中待检测对象的锚定框的位置标注信息，位置标注信息包括锚定框相对于预设方向的角度信息；基于目标检测模型获取第一遥感图像的目标特征图，基于目标特征图对待检测对象进行目标检测，得到目标边界框，并基于角度信息，确定锚定框和目标边界框之间的损失信息；基于损失信息，更新目标检测模型的参数。根据本申请的技术，解决了目标检测技术中存在的对遥感图像的目标检测准确率比较低的问题，提高了对遥感图像的目标检测的准确率。 This application discloses an object detection model training method, object detection method and related apparatus, and relates to the field of artificial intelligence technologies such as computer vision, deep learning. A specific implementation includes: obtaining training sample data including a first remote sensing image and position annotation information of an anchor box of a subject to be detected in the first remote sensing image, where the position annotation information includes angle information of the anchor box relative to a preset direction; obtaining an object feature map of the first remote sensing image based on an object detection model, performing object detection on the subject to be detected based on th